Revitalizing Islamic Philanthropy: The Role of Cash Waqf in Pakistan’s Socioeconomic Development - Abdeen, Zain ul; Junaid, Muhammad (Islamic Banking and Finance Review, 2026)
The emergence of Cash Waqf as one of the most important Islamic social finance tools that can tackle poverty, inequality, educational deprivation and socioeconomic exclusion in Muslim societies, is one of the most remarkable phenomena in the Islamic financial landscape in recent years. In the modern Islamic economy, Cash Waqf is gaining ground as a viable instrument for funding welfare programs and development projects by individuals through charitable donations and institutional investments. This study aimed to analyze the contribution of Cash Waqf in the socioeconomic development of Pakistan in terms of public perception about Cash Waqf’s contribution in poverty alleviation, educational advancement, healthcare support, employment generation and religious and institutional development. The study was conducted with descriptive and exploratory research design with a disproportionate stratified random sampling technique. The primary data were gathered from 200 respondents in Islamabad between January and March 2025 using a structured questionnaire and interviews. Descriptive statistical techniques were applied in analyzing the perceptions on the effectiveness and developmental potentials of Cash Waqf. The findings show the high level of public acceptance of the use of Cash Waqf for poverty alleviation, health care funding, education support and employment generation. In addition, respondents showed medium-level confidence in the role of Cash Waqf in religious institutions like madrassas, mosques and the charities based on shrines in religious institutions. The study also notes that the governance, transparency, institutional trust, and public awareness are also important factors in the effective implementation of Cash Waqf systems in Pakistan. Based on the comparative experiences of Malaysia, Indonesia, Turkey, Kuwait and Saudi Arabia, the study makes the argument that Cash Waqf has ample scope and potential to be institutionalized as a viable Islamic social finance mechanism in Pakistan.